Whole-genome sequencing analysis of structural variants in oesophageal adenocarcinoma. (23rd February 2017) - Contino, Gianmarco; Secrier, Maria; Edward, Paul A W; Fitzgerald, Rebecca
Abstract: Background: The incidence of oesophageal adenocarcinoma is increasing substantially. Sequencing studies have highlighted that this tumour is highly heterogeneous, with few recurrent point-mutations. Structural variants (SVs) are large mutations that can be inferred from whole-genome sequencing data and are emerging as a major component of the mutational landscape of this cancer. The aim of this study was to carry out a detailed characterisation of SVs in oesophageal cancer. Methods: Snap-frozen endoscopic biopsy samples and surgical specimens were collected from 289 patients with oesophageal cancer in a nationwide collaborative effort (Oesophageal Cancer Clinical and Molecular Stratification Collaboration). A single library was created for each sample, and paired-end sequencing was performed (Illumina, San Diego, CA, USA) to a typical depth of at least 50 ×. Structural variants were detected by an in-house clustering tool that clusters discordant and split reads (v0.55). Only somatic structural variants with four supporting reads were used in the analysis. Findings: We identified 48 different genes that were hit by SVs in more than 29 patients (>10%) and as many as 273 hits in more than 15 (5%). PCR verification confirmed the presence of the predicted SVs in more than 90% of cases in a subset of 98 analysed rearrangements. By contrast, in this cancer only seven genes have been reported as recurrently mutated by point-mutations in over 10% of cases, making structural variation the most common mechanism for recurrent mutations of oesophageal adenocarcinoma. Among the recurrently mutated genes, we found significant enrichment for two main pathways: cell–cell communication and cell–extracellular matrix organisation (p<10E −7 ) and ErbB signalling/FGFR (p<10E −3 ). In particular, we identified a subset of 20 genes including master regulator of desmosome ( JUP ), integrins ( PTK2 ), and catenins ( CTNNA3 and CTNNA3 ). We also identified SVs in CTNNA3 as a prognostic marker of poor survival in our cohort (p=0·003). Interpretation: SVs are a common mechanism for recurrent mutations in oesophageal adenocarcinoma. Genes recurrently mutated by SVs point to a small number of pathways that are potentially relevant to disease progression and prognosis. Funding: National Institute for Health Research, Cancer Research UK.